For the Fourier transform of the convolution in and D’ and Z’ - Rechkoski, Vasko; Bedzeti, Bedrije; Erakovikj, Vesna Manova (JOURNAL OF ADVANCES IN MATHEMATICS, 2021)
In this paper, we give another proof of the known lemma considering the Fourier transform of the convolution of a distribution and a function. Also, we give its application in the mentioned spaces.